TRENING AKULTURACYJNY A ROZWIJANIE INTERKULTUROWEJ KOMPETENCJI KOMUNIKACYJNEJ - Janowska, Iwona; Bodzioch, Marta (Neofilolog, 2018)
The article introduces the concept of language lessons based on an accul-tural training model in a type of a simulation that was presented in a re-action to the current inquires on the role of culture in glottodydactics. The goal of such lessons is to develop students’ intercultural communica-tion skills through the task-solving method. The central point of the arti-cle is the author’s personal lessons conducted via a training script.